Uncovering the roles of long noncoding RNAs in neural development and glioma progression. (20th June 2016) - Ramos, Alexander D.; Attenello, Frank J.; Lim, Daniel A.
Abstract: In the past decade, thousands of long noncoding RNAs (lncRNAs) have been identified, and emerging data indicate that lncRNAs can have important biological functions and roles in human diseases including cancer. Many lncRNAs appear to be expressed specifically in the brain, and the roles of lncRNAs in neural stem cells (NSCs) and brain development are now beginning to be discovered. Here we review recent advances in understanding the diversity of lncRNA structure and functions in NSCs and brain development. NSCs in the adult mouse ventricular–subventricular zone (V–SVZ) generate new neurons throughout life, and we discuss how key elements of this adult neurogenic system have facilitated the discovery and functional characterization of known and novel lncRNAs. A review of lncRNAs described in other NSC systems reveals a variety of molecular mechanisms, including binding and recruitment of transcription factors, epigenetic modifiers, and RNA-splicing factors. Finally, we review emerging evidence indicating that specific lncRNAs can be key drivers of glial tumors, and discuss next steps towards an in vivo understanding of lncRNA function in development and disease.